Electromagnetic characteristics of in vivo nerve fibers at the terahertz-far-infrared band - Guo, Lianghao; Xu, Duo; Wang, Kaicheng; Sun, Yuankun; Zhang, Qin; Ning, Hui; Lu, Chang; Wang, Shaomeng; Gong, Yubin (Frontiers in Bioengineering and Biotechnology, 2022)
In the life sciences community, it has attracted widespread interest in how terahertz signals perform in the neural system. Relevant experimental reveals that in animal nerve cells, the myelin sheath of nerve axon has a higher refractive index than the intracellular and extracellular fluids in the Terahertz-far-infrared (THz-FIR) frequency band, making it possible for THz-FIR waves transmission nerve fibers. Based on this premise, this paper carries out the following work from the theoretical level to investigate the electromagnetic (EM) characteristics of in vivo nerve fibers at the THz-FIR band. First, the EM transmission model of the nerve fibers is established and studied theoretically. The dispersion curves of THz-FIR wave modals transmission in nerve fibers are calculated, predicting that the nerve fibers can act as dielectric waveguides for transmitting THz-FIR waves and the THz-FIR waves can transmit at speeds up to 108m/s. Second, a mode matching algorithm is proposed, named RNMMA to calculate the transmission characteristics of THz-FIR waves at the nodes of Ranvier. The scattering matrix obtained from the proposed algorithm is in good agreement with the results from EM simulation software, which reveals how THz-FIR signals are transmitted forward through the nodes of Ranvier with low loss.